Function f : R → R is such that f ( x + y ) = f ( x ) + f ( y ) − x y − 1 for all x , y ∈ R and that f ( 1 ) = 1 .
Find the number of solutions to f ( n ) = n , where n ∈ N .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
as usual great and perfect solution sir ,, thanks for solving .
Log in to reply
Hey bro , How's life?
Log in to reply
hey bro , it is fine but bit struggling ,, what about you .. are you having gmail account ??
I too am struggling, especially in chemistry. Yes i have a gmail account , you should come to slack.
Log in to reply
@Aditya Chauhan – but i don't know how to get on slack ?? i have not used it earlier ,
Log in to reply
@Rudraksh Sisodia – https://brilliant.slack.com/signup
How do you know f(1)=1 ??? I cant understand this part
Log in to reply
Sorry, I edited the problem without including f ( 1 ) = 1 back.
actually @Kushal Bose it is the editted question by the editors , i have given f(1) =1 in my original question .. but now i don't know how to edit it again ,,
Log in to reply
Sorry, I edited the problem and forgetting about the f ( 1 ) = 1 part.
Also, we get an explicit formula for f ( n ) whenever n ∈ N , which is f ( n ) = 1 − 2 n ( n − 1 ) .
@Samrat Mukhopadhyay , please can you explain the way of using explicit formula ?? and even what is it ?
Damn, I neglected the fact that natural numbers did not include negatives and thought the answer was two since "-2" is a solution as well.
Put y=0 and you will get f ( 0 ) = 1 . Now, put f(0) in place of 1 in the question and divide by 'y' and put the limit y → 0 . Using constraint that f ( 0 ) = f ( 1 ) = 1 , you will get f ( x ) = x / 2 − x 2 / 2 + 1
its not hard to see its a continuous function which map to itself , by applying fixed point theorem ,there must be at least one value for f(n)=n
Problem Loading...
Note Loading...
Set Loading...
f ( x + y ) ⟹ f ( n + 1 ) ⟹ f ( n + 1 ) = f ( x ) + f ( y ) − x y − 1 = f ( n ) + f ( 1 ) − n − 1 = f ( n ) + 1 − n − 1 = f ( n ) − n Putting x = n , y = 1
For n ∈ N , we note that f ( n + 1 ) < f ( n ) . Since f ( 1 ) = 1 , f ( n ) ≤ 0 for n > 1 . Therefore, there is only 1 n such that f ( n ) = n , that is f ( 1 ) = 1 .